Maternal consumption of cigarette during pregnancy and low birth weight: case-control study (Research, Society and Development, 2020)
The birth weight of newborn is an indicator that reflects maternal health conditions and the healthcare quality delivered during pregnancy. The aim of this study is to analyze the association between maternal consumption of cigarette during pregnancy and Low Birth Weight (LBW) in the Northeast of Brazil. Case-control study with the group of cases composed of 402 mothers with newborns with a birth weight